2022
DOI: 10.26434/chemrxiv-2022-4q2pd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systemic anti-tumor immunity mediated by photodynamic therapy using injectable chitosan hydrogels for intra-tumoral and sustained drug delivery

Abstract: Photodynamic therapy (PDT) is an anti-cancer therapy with proven efficacy; however, its application is often limited by prolonged skin photosensitivity and solubility issues associated with the phototherapeutic agents. Injectable hydrogels that can effectively provide intra-tumoral delivery of photosensitizers with sustained release is attracting increased interest for photodynamic cancer therapies. However, most of the hydrogels for PDT applications are based on systems with high complexity and often, pre-cli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Another superiority of the CS−drug conjugate approach for CS modification is that it confers the CS-based hydrogels with some biological activities such as anti-inflammatory, 41 antioxidative, 42 and antitumor. 43 The low methacrylation degree of CS−MA results in poor physicochemical properties of the hydrogels (Figure 5). In our experiments, it can be found that GA−CS−MA had a higher degree of methacrylation (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Another superiority of the CS−drug conjugate approach for CS modification is that it confers the CS-based hydrogels with some biological activities such as anti-inflammatory, 41 antioxidative, 42 and antitumor. 43 The low methacrylation degree of CS−MA results in poor physicochemical properties of the hydrogels (Figure 5). In our experiments, it can be found that GA−CS−MA had a higher degree of methacrylation (Figure 3).…”
Section: Discussionmentioning
confidence: 99%